The impact of a cash transfer programme on tuberculosis treatment success rate: a quasi-experimental study in Brazil - Daniel J Carter; Rhian Daniel; Ana W Torrens; Mauro N Sanchez; Ethel Leonor N Maciel; Patricia Bartholomay; Draurio C Barreira; Davide Rasella; Mauricio L Barreto; Laura C Rodrigues; Delia Boccia (BMJ Global Health)
Background Evidence suggests that social protection policies such as Brazil’s Bolsa Família Programme (BFP), a governmental conditional cash transfer, may play a role in tuberculosis (TB) elimination. However, study limitations hamper conclusions. This paper uses a quasi-experimental approach to more rigorously evaluate the effect of BFP on TB treatment success rate.Methods Propensity scores were estimated from a complete-case logistic regression using covariates from a linked data set, including the Brazil’s TB notification system (SINAN), linked to the national registry of those in poverty (CadUnico) and the BFP payroll.Results The average effect of treatment on the treated was estimated as the difference in TB treatment success rate between matched groups (ie, the control and exposed patients, n=2167). Patients with TB receiving BFP showed a treatment success rate of 10.58 percentage points higher (95% CI 4.39 to 16.77) than patients with TB not receiving BFP. This association was robust to sensitivity analyses.Conclusions This study further confirms a positive relationship between the provision of conditional cash transfers and TB treatment success rate. Further research is needed to understand how to enhance access to social protection so to optimise public health impact.